(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
The present study was carried out to determine the combining ability of yield and yield components by crossing six diverse maize inbred lines in a half diallel mating design. Fifteen F1 progenies along with their six parents were planted in randomized complete block design with three replications. GCA to SCA ratios were less than one for plant height, cob diameter, cob length and number of kernels row/cob indicating a preponderance of additive over non additive gene action. The crosses P1×P2, P3×P5 and P5×P6 were exhibited significant and positive SCA effects for yield and cob diameter, number of row/cob and number of grains/cob of yield contributing characters. The parents P1 (IL4), P3 (IL18)and P5 (IL23 were good general combiner for grain yield and yield attributing characters. It can be concluded that these parental lines can be desirable parents for hybrids as well as for inclusion in breeding program, since they may contribute favorable alleles in the synthesis of new varieties.